Electricity generation through microbial fuel cells utilizing leftover rice as food waste - Mohd Nasir, Mohamad Na'im; Abdul Rashid, Ahmad Amirul Fitri; Bohari, Zul Hasrizal; Yahaya, Muhamad Sharil; Sulaima, Mohamad Fani; Nanyan, Ayob Nazmy (Semarak Ilmu Publishing, 2023)
Organic food waste management has been a major issue for the environment, as it poses a significant threat to human health and the ecosystem. Converting this waste into a valuable resource is crucial for sustainable development. In this project, we aim to develop a microbial fuel cell (MFC) using leftover rice as a substrate, which can generate electricity through the electrochemical reactions of microorganisms. The main objectives of this study are to investigate the performance of MFCs under two different conditions: with and without a mediator and catalyst. The experimental results showed that both designs of MFCs achieved optimized outputs, with a minimum of 5V voltage output. This demonstrates the potential of MFCs as a promising alternative renewable energy source. MFCs can be utilized as a sustainable energy source, particularly for rural areas, where access to electricity is limited. Furthermore, large-scale operation of MFCs can significantly reduce food waste, which has a significant impact on health and the environment. By converting food waste into electricity, this technology can help mitigate the negative effects of waste accumulation and contribute to the transition towards a circular economy.